Features of Heart Rate Variability in Polar Explorers Under Whole Body Short-Term Air Cooling - Vysokosova, Alona (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 295